2019
DOI: 10.31545/intagr/110808
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wood anisotropy on its mechanical properties in relation to the scale effect

Abstract: As a construction material wood is characterized by many advantages: low density, a high degree of strength and stiffness, low thermal and electrical conductivity and chemical durability. However, it is an anisotropic material that contains structural elements of varying stiffness and strength. When moisture levels increase, it is characterized by the variability of its mechanical properties and creep resulting from rheological properties. Therefore, it is important to understand how the mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In this case, it depends on the specific type or type of the material and may only affect the mechanical or physical properties of the tested samples. Depending on the materials tested, the influence of anisotropy on the values of capillary rise, compressive strength, tensile strength, and thermal conductivity was demonstrated [ 2 , 3 , 4 , 5 , 6 ]. The influence of the anisotropy phenomenon can be observed in the materials of organic origin.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it depends on the specific type or type of the material and may only affect the mechanical or physical properties of the tested samples. Depending on the materials tested, the influence of anisotropy on the values of capillary rise, compressive strength, tensile strength, and thermal conductivity was demonstrated [ 2 , 3 , 4 , 5 , 6 ]. The influence of the anisotropy phenomenon can be observed in the materials of organic origin.…”
Section: Introductionmentioning
confidence: 99%
“…The MOE values exhibited slight differences across the various length groups, under same testing method, ranging from 0.6% to 4.5%. Given the inherent variability due to the anisotropy of the wood material [ 34 ], the testing results in this study are considered reliable. It was concluded that, under the same testing method, the length effect does not significantly impact the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…To date, hardness tests have been performed mainly on vegetables or fruits containing large amounts of water and those with low water content, e.g., cereal seeds, legume plants, wood etc. [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Interestingly, this parameter has often been assessed using a conventional scale, as in the case of pomegranate ( Punica granatum L.) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%